Structure and conductivity of epitaxial thin films of barium ferrite and its hydrated form BaFeO2.5−x+δ(OH)2x. (14th February 2017) - Sukkurji, Parvathy Anitha; Molinari, Alan; Benes, Alexander; Loho, Christoph; Chakravadhanula, Venkata Sai Kiran; Garlapati, Suresh Kumar; Kruk, Robert; Clemens, Oliver
Abstract: Barium ferrite and its hydrated form (BaFeO2.5− x + δ (OH)2 x, BFO) is an interesting cathode material for protonic ceramic fuel cells (PCFC) due to its potential to be both, conducting for electrons and protons. We report on the fabrication of almost epitaxially grown thin films (22 nm) of barium ferrite BaFeO 2.5 (BFO) on Nb-doped SrTiO3 substrates via pulsed laser deposition (PLD), followed by treatment under inert, and subsequently wet inert atmospheres to induce water (respectively proton) incorporation. Microstructure, chemical composition and conducting properties are investigated for the BFO films and their hydrated forms, highlighting the influence of hydration on the conductivity characteristics between 200–290 K. We find that water incorporation gives a strong enhancement of the conductivity to 10 −9 S cm −1 compared to argon annealed films, inducing electronic and protonic charge carriers at the same time. In comparison to bulk powders, proton conductivity is found to be strongly suppressed in such thin hydrated BFO films, pointing towards the influence of strain on the conductivity, which is evaluated based on a detailed investigation by high-resolution transmission electron microscopy.